2004
DOI: 10.1086/381941
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of the Genetic Variance‐Covariance Matrix and the Fitness Surface for Multiple Male Sexually Selected Traits

Abstract: Stabilizing selection has been predicted to change genetic variances and covariances so that the orientation of the genetic variance-covariance matrix (G) becomes aligned with the orientation of the fitness surface, but it is less clear how directional selection may change G. Here we develop statistical approaches to the comparison of G with vectors of linear and nonlinear selection. We apply these approaches to a set of male sexually selected cuticular hydrocarbons (CHCs) of Drosophila serrata. Even though ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
388
3
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(411 citation statements)
references
References 57 publications
(90 reference statements)
12
388
3
8
Order By: Relevance
“…Other studies, however, suggest that the number of dimensions can be reasonably high (Mezey and Houle, 2005). It seems to me that the number of dimensions usually will be very high, certainly much higher than suggested by the current analyses of suites of very similar traits, such as cuticular hydrocarbons (Blows et al, 2004) or wing shape (Mezey and Houle, 2005;McGuigan and Blows, 2007). The reason is that overall adaptation to a given environment will inevitably involve a host of morphological, life history, physiological and behavioral changes, which will not collapse down to only a few dimensions.…”
Section: Ecosystem Functionmentioning
confidence: 53%
“…Other studies, however, suggest that the number of dimensions can be reasonably high (Mezey and Houle, 2005). It seems to me that the number of dimensions usually will be very high, certainly much higher than suggested by the current analyses of suites of very similar traits, such as cuticular hydrocarbons (Blows et al, 2004) or wing shape (Mezey and Houle, 2005;McGuigan and Blows, 2007). The reason is that overall adaptation to a given environment will inevitably involve a host of morphological, life history, physiological and behavioral changes, which will not collapse down to only a few dimensions.…”
Section: Ecosystem Functionmentioning
confidence: 53%
“…They found that the divergence of traits that were likely to be under strong selection showed less evidence of being affected by correlations than traits that were less likely to be targets of strong selection. Blows et al (2004) examined the relationship between G and selection by measuring the angle between b and the projection of the 'major' subspace of G onto b, and by comparing the angles between the axes of major subspaces of G and g. As with our metric, this approach is intended to give a sense of the extent to which patterns of genetic variation constrain or facilitate evolution. This approach can be useful when applied to systems where the biology is well understood and the results are carefully interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…First, the resulting metrics are not simple to understand or interpret. Second, the choice of principal component axes used to define the subspaces is somewhat arbitrary, and not all of the principal component axes can be used (Blows et al 2004). Third, it is possible for this approach to give misleading results when only one or a few of the correlated traits are under selection unless results are interpreted with great caution.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of the eigenvalues of S gives a bounded statistic, which ranges between complete orthogonality (0) and complete overlap (k) of the two subspaces, respectively. Blows et al (2004) give further details on the use of this approach for comparing G-matrices and second-order fitness surfaces.…”
Section: Methods 2 Krzanowski's Common Subspacesmentioning
confidence: 99%